Cardiovascular, cognitive, and mental health benefits of running and walking: A literature review - Arfanda, Poppy Elisano; Aprilo, Ians; Mappaompo, M. Adam -; Awaluddin, Awaluddin; Arimbi, Arimbi; Muhammad, Heryanto Nur (Jurnal Ilmu Keolahragaan, 2025)
Background. Cardiovascular disease, cognitive decline, and mental health disorders are becoming increasingly prevalent worldwide, posing serious threats to public health and individual well-being. These conditions often stem from sedentary lifestyles, poor cardiovascular fitness, and lack of consistent physical activity. As such, identifying effective and accessible strategies for prevention and management is crucial. Objectives. This literature review aims to evaluate the impact of running and walking"”two of the most common and accessible forms of physical activity"”on cardiovascular health, cognitive function, and mental well-being. The goal is to determine the extent to which these activities contribute to the prevention and improvement of such health conditions. Methods. This study employed the Systematic Literature Review (SLR) method to analyze 70 selected peer-reviewed articles published between 2014 and 2024. Articles were retrieved from reputable academic databases including Google Scholar, Scopus, Science Direct, Web of Science, and Crossref. The keywords used for selection included "cardiovascular health," "physical activity," "mental health," "cognitive," "running," and "walking." Results. Findings indicate that running is strongly associated with enhanced cardiovascular function, reduced risk of cognitive impairment, and improved mental health through increased blood circulation and brain activity. Walking, although lower in intensity, also showed significant benefits, particularly for older adults or individuals with limited physical capacity. Conclusion. Both running and walking are effective, non-pharmacological interventions for improving cardiovascular, cognitive, and mental health outcomes. While running provides more robust physiological benefits, walking remains a widely accessible and sustainable option for most populations.